Individual and geographic disparities in human papillomavirus types 16/18 in high-grade cervical lesions: Associations with race, ethnicity, and poverty. - Niccolai, Linda M; Russ, Chelsea; Julian, Pamela J; Hariri, Susan; Sinard, John; Meek, James I; McBride, Vanessa; Markowitz, Lauri E; Unger, Elizabeth R; Hadler, James L; Sosa, Lynn E (Cancer, 2013)
BACKGROUND: Current vaccines protect against 2 human papillomavirus (HPV) types, HPV 16 and 18, which are associated with 70% of cervical cancers and 50% of high-grade cervical lesions. HPV type distribution was examined among women with high-grade lesions by individual and area-based measures of race, ethnicity, and poverty. METHODS: This analysis included 832 women aged 18 to 39 years reported to a surveillance registry in Connecticut during 2008 to 2010. Diagnostic specimens were obtained for HPV DNA testing. Individual measures were obtained from surveillance reports, medical records, and patient interviews. Cases were geocoded to census tracts and linked to area-based measures of race, ethnicity, and poverty. Statistical analysis included use of generalized estimating equations. RESULTS: Overall, 44.8% of women had HPV 16/18. In a multivariate model controlled for confounding by age and diagnosis grade, black race (adjusted prevalence ratio [aPR] = 0.54, 95% confidence interval [CI] = 0.34-0.88), Hispanic ethnicity (aPR = 0.59, 95% CI = 0.40-0.88), and higher area-based poverty (aPR = 0.59, 95% CI = 0.40-0.87) were associated with a lower likelihood of HPV 16/18 positivity. Black and Hispanic women were less likely to have HPV 16/18 than white women across all levels of area-based measures. CONCLUSIONS: Black race, Hispanic ethnicity, and higher area-based poverty are salient predictors of lower HPV 16/18 positivity among women with high-grade cervical lesions. These data suggest that HPV vaccines might have lower impact among black and Hispanic women and those living in high poverty areas. These findings have implications for vaccine impact monitoring, vaccination programs, and new vaccine development. Cancer 2013; © 2013 American Cancer Society.